Lived memories, felt stories in the Americas and Africa: the invention of a Community (Research, Society and Development, 2020)
This article analyzes the invention of a Community Museum with students from the University of International Integration of Afro-Brazilian Lusophony (UNILAB) in Ceará. This experience was lived from the curricular component Literacy, Literacy and Bilingualism in the Countries of Integration, in the Pedagogy Course. The initiative aimed to problematize the processes of non-formal, informal education and the schooling of students and their ancestors, based on lived memories and felt stories in the Americas and in Africa, in the communities that are part of the South-South solidarity cooperation. We revisited the systematized experiences of community museums, the autobiographical literature of childhood and schooling, from Brazilian and African writers and we chose as categories of analysis the felt history, lived memory, time, space, educations and literacy. The qualitative, descriptive-analytical study focuses on autobiographical and biographical research, with emphasis on 21 student narratives, 3 from Guinea and 18 from Brazil. As data collection procedures, we highlight participant observation, iconographic record, individual assessment of pedagogical practice and portfolios. The dialogue between students provided a subjective and collective interpretation on the importance of rescuing ancestry in the process of teacher education and the performance of future educators in school and non-school spaces.